2012
DOI: 10.1073/pnas.1121103109
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Ca 2 + current conducted by voltage-gated Ca 2+ (Ca V )-2.1 and Ca V 2.2 channels and its implications for asynchronous neurotransmitter release

Abstract: We have identified an asynchronously activated Ca 2+ current through voltage-gated Ca 2+ (Ca V )-2.1 and Ca V 2.2 channels, which conduct P/Qand N-type Ca 2+ currents that initiate neurotransmitter release. In nonneuronal cells expressing Ca V 2.1 or Ca V 2.2 channels and in hippocampal neurons, prolonged Ca 2+ entry activates a Ca 2+ current, I Async , which is observed on repolarization and decays slowly with a halftime of 150-300 ms. I Async is not observed after L-type Ca 2+ currents of similar size conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Another recent paper reports that the SNARE protein VAMP2 drives synchronous release, while its isoform VAMP4 boosts asynchronous release14. Moreover, it was recently shown that both voltage-gated presynaptic Cav-2.1 and Cav-2.2 channels, that conduct P/Q-type and N-type Ca 2+ currents respectively, are characterized by a prolonged Ca 2+ current that promotes asynchronous release49.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent paper reports that the SNARE protein VAMP2 drives synchronous release, while its isoform VAMP4 boosts asynchronous release14. Moreover, it was recently shown that both voltage-gated presynaptic Cav-2.1 and Cav-2.2 channels, that conduct P/Q-type and N-type Ca 2+ currents respectively, are characterized by a prolonged Ca 2+ current that promotes asynchronous release49.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that voltage-gated Ca 2+ channels provide the brief Ca 2+ signal that evokes synchronous release, but voltage-gated Ca 2+ channels may also provide a longer-lasting phase of Ca 2+ entry that may contribute to asynchronous release (157). In transfected nonneuronal cells, following a large and prolonged depolarization or a train of depolarizations, a fraction of either Ca V 2.1 (P-type) or Ca V 2.2 (N-type) Ca 2+ channels open for hundreds of milliseconds.…”
Section: Asynchronous Releasementioning
confidence: 99%
“…Intriguingly, P/Q- and N-type VACCs, which trigger evoked release, will also activate sustained calcium entry following prolonged activation. This “asynchronous” Ca 2+ current decays over hundreds of milliseconds, and may directly trigger asynchronous release [91]. TRPV1, the Ca 2+ permeable non-selective cation channel, is another ion channel that may evoke asynchronous release but unlike P/Q- and N-type VACCs TRPV1 will not trigger synchronous release [6].…”
Section: Asynchronous Release – More Than One Mechanismmentioning
confidence: 99%